2012
DOI: 10.1177/0018720811434512
|View full text |Cite
|
Sign up to set email alerts
|

Use Patterns Among Early Adopters of Adaptive Cruise Control

Abstract: Potential applications of this research include enhanced design for next-generation ACC systems and countermeasures to improve safe driving with ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Drivers with a risky driving style were generally younger and more likely to drive and use ACC (Figure 1), which is consistent with previous research showing that the use of ACC (e.g., the headway set by the driver) is a function of the driver's age and driving style (Cicchino and McCartt 2015;Jenness et al 2008;Wu and Boyle 2015;Xiong et al 2012). Moreover, these results are coherent with previous questionnaire and observational research in manual driving showing that young drivers are more likely to commit traffic violations than older drivers (de Winter et al 2015;Martinussen et al 2014;Parker et al 1995).…”
Section: Correlates Of Acc Pleasantness and Risky Driving Stylesupporting
confidence: 89%
“…Drivers with a risky driving style were generally younger and more likely to drive and use ACC (Figure 1), which is consistent with previous research showing that the use of ACC (e.g., the headway set by the driver) is a function of the driver's age and driving style (Cicchino and McCartt 2015;Jenness et al 2008;Wu and Boyle 2015;Xiong et al 2012). Moreover, these results are coherent with previous questionnaire and observational research in manual driving showing that young drivers are more likely to commit traffic violations than older drivers (de Winter et al 2015;Martinussen et al 2014;Parker et al 1995).…”
Section: Correlates Of Acc Pleasantness and Risky Driving Stylesupporting
confidence: 89%
“…speed reduction) for ACC users when approaching curves or entering fog, while Dixit, Chand, and Nair (2016) showed that reaction times in taking control of the vehicle after disengagement of the autonomous mode increases with vehicle miles travelled. Xiong, Boyle, Moeckli, Dow, and Brown (2012) showed that drivers' adaptive behaviorand therefore the safety implications of ACC-is related to trust in automation, driving styles, understanding of system operations and the driver's personality. Furthermore, safety levels might not substantially increase (or even decrease) until high penetration rates of fully automated vehicles are realized.…”
Section: Literature Resultsmentioning
confidence: 99%
“…However, inappropriate perceptions may actually lead to greater use at inappropriate times (Parasuraman & Riley, 1997). Xiong, Boyle, Moeckli, Dow, and Brown (2012) showed that drivers who tended to over-trust the system might be more likely to have more ACC warnings and respond later to critical events.…”
Section: Introductionmentioning
confidence: 99%